Domestic violence during pregnancy and risk of low birthweight and maternal complications: a prospective cohort study at Mulago Hospital, Uganda - Kaye, Dan K.; Mirembe, Florence M.; Bantebya, Grace; Johansson, Annika; Ekstrom, Anna Mia (Tropical Medicine & International Health, 2006)
To investigate whether domestic violence during pregnancy is a risk factor for antepartum hospitalization or low birthweight (LBW) delivery. A prospective cohort study was conducted in Mulago hospital, Kampala, Uganda, among 612 women recruited in the second pregnancy trimester and followed up to delivery, from May 2004 through July 2005. The exposure (physical, sexual or psychological violence during pregnancy) was assessed using the Abuse Assessment Screen. The relative and attributable risks of LBW and antepartum hospitalization were estimated using multivariate logistic regression analysis. The 169 women [27.7% 95% CI (24.3–31.5%)] who reported domestic violence during pregnancy did not differ significantly from the unexposed regarding sociodemographic characteristics, but differed significantly (P < 0.05) regarding domicile variables (had less household decision-making power, more resided in extended families and more had unplanned pregnancy). They delivered babies with a mean birthweight 2647.5 ± 604 g, on average 186 g [(95% CI 76–296); P ¼ 0.001] lower than those unexposed. After adjusting for age, parity, number of living children, pregnancy planning, domicile and number of years in marriage, the relative risk (RR) of LBW delivery among women exposed to domestic violence was 3.78 (95% CI 2.86–5.00). Such women had a 37% higher risk of obstetric complications (such as hypertension, premature rupture of membranes and anaemia) that necessitated antepartum hospitalization [RR 1.37 (95% CI 1.01–1.84)]. In this pregnancy cohort, domestic violence during pregnancy was a risk factor for LBW delivery and antepartum hospitalization.
Keywords: Domestic violence; Pregnancy; Low birthweight; Antepartum hospitalization; Relative and attributable risk; Uganda